Do Not Miss the Snake in the Grass – An Interesting Case Series of Mimics in Pap Smear Cytology Which May Impact Reporting - Nidha Gaffoor; Archana Shetty (Archives of Medicine and Health Sciences)
Microscopic examination remains a major component in a diagnostic cytopathology laboratory. Pap smears are one among the commonly reported tests in gynecologic pathology. It is not infrequent to routinely come across artifactual or less significant cytological findings that closely mimic relevant reportable findings both on liquid-based and conventional Pap smear examinations. To an imprudent examiner, this not only results in a merry chase but also affects the quality of the final report generated. We present a series of microscopic findings on Pap smears, encountered over 3 months in our laboratory with their close resembles with a note on points of differentiation. This case series is presented with the intent to highlight the need for cytopathologists to be aware of the potential diverters and avoid overdiagnosing or underlooking findings which may have clinical implications.